HCV Genotype Distribution Among People Who Inject Drug in Turkey: Findings from Multicenter and Cross-Sectional Study - Nesrin Dilbaz; Murat Kuloğlu; Ekrem Cuneyt Evren; Salih Cihat Paltun; Rabia Bilici; Cemal Onur Noyan; Burak Kulaksizoglu; Vahap Karabulut; Gokhan Umut; Basak Unubol; Enver Ucbilek (SAGE Publishing, 2023)
Background: Hepatitis C virus (HCV) infection is very common in people who inject drugs (PWID). Studies about the prevalence and genotype distribution of the HCV among PWID are very crucial for developing strategies to manage HCV infection. This study's objective is to map the distribution of HCV genotypes among PWID from various regions of Turkey. Method: This prospective, multicenter, cross-sectional study involved 197 PWID who tested positive for anti-HCV antibodies from 4 different addiction treatment facilities in Turkey. Interviews were done with people who had anti-HCV antibodies, and blood samples were taken to check the HCV RNA viremia load and genotyping. Results: This study was conducted on 197 individuals with a mean age of 30.3 ± 8.6 years. 9.1% (136/197 patients) had a detectable HCV-RNA viral load. Genotype 3 was the most commonly observed genotype by 44.1%, followed by genotype 1a by 41.9%, genotype 2 by 5.1%, genotype 4 by 4.4%, and genotype 1b by 4.4%. Whereas genotype 3 was dominant with 44.4% at the central Anatolia region of Turkey, the frequencies of genotypes 1a and 3, which were predominantly detected in the south and northwest regions of Turkey, were very close to each other. Conclusion: Although genotype 3 is the predominant genotype in the PWID population in Turkey, the prevalence of HCV genotype varied across the country. To eliminate HCV infection in the PWID, treatment and screening strategies that differ by genotype are essentially required. Especially identification of genotypes will be useful in developing individualized treatments and determining national prevention strategies.